2021
DOI: 10.3389/fpls.2021.690040
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Function of Aquaporin Genes During Dormancy and Sprouting Periods of Kernel-Using Apricot (Prunus armeniaca L.)

Abstract: Aquaporins (AQPs) are essential channel proteins that play a major role in plant growth and development, regulate plant water homeostasis, and transport uncharged solutes across biological membranes. In this study, 33 AQP genes were systematically identified from the kernel-using apricot (Prunus armeniaca L.) genome and divided into five subfamilies based on phylogenetic analyses. A total of 14 collinear blocks containing AQP genes between P. armeniaca and Arabidopsis thaliana were identified by synteny analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…Single or co-overexpression of genes in yeast to test their effects on abiotic stressors is a tried-and-true method, as shown by a number of research studies. , Individually or in combination, the genes VaCOLD1 and VaGPA1 were introduced into yeast expression vectors and subsequently transformed into W303 (Figure A) to examine their functions in cold tolerance. Under normal circumstances, growth of both nontransformed and transgenic strains was comparable (Figure B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Single or co-overexpression of genes in yeast to test their effects on abiotic stressors is a tried-and-true method, as shown by a number of research studies. , Individually or in combination, the genes VaCOLD1 and VaGPA1 were introduced into yeast expression vectors and subsequently transformed into W303 (Figure A) to examine their functions in cold tolerance. Under normal circumstances, growth of both nontransformed and transgenic strains was comparable (Figure B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Further, in Arabidopsis [ 12 ], the PIP subfamily had the most AQP members with 13 members, but in M. sativa , the TIP subfamily had the most AQP members, with 17 members ( Table 1 ), which may be the main reason for the expansion of the AQP gene family in M. sativa . It is interesting that XIPs were identified from some plants, such as the common bean, nicotiana glauca , tea plant, apricot [ 20 , 21 , 23 , 46 ], however, XIP was absent in M. sativa as in Arabidopsis and Brassica rapa [ 12 , 31 ], which indicated that XIPs might be unique for specific families of plant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that almost one third of total MsAQP proteins lost one or more of the conserved domains, at least one to three transmembrane domains or one NPA domain ( Figure S1 ). By contrast, the length of the deduced AQP proteins ranged from 240 to 323 aa in A. thaliana [ 12 ], from 219 to 329 aa in apricots [ 21 ], 236 to 326 aa in tea plants [ 20 ]. Even in the close relative of M. truncatula , the length of the majority of MtAQPs fell into the range of 218–330 aa ( Table S1 ), therefore, we suspected that the lack of partial gene sequences may be due to the incompleteness of the genome assembly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations